Investigation of cardiotoxic effects of marbofloxacin - Devran Coşkun; Burak Dik; Yasemin Korkmaz; Rahmi Canbar; Ayşe Er; Enver Yazar (Eurasian Journal of Veterinary Sciences)
Aim: The primary objective of the present research is to determine the cardiotoxic effect of marbofloxacin by measuring of serum troponin I, creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) levels which are cardiotoxic damage markers. In addition, it is to determine the effects of marbofloxacin on the liver function [alkaline phosphatase (ALP), alanine aminotransferase (ALT), gamma glutamyltransferase (GGT), total protein], renal function [blood urea nitrogen (BUN, creatinine] and hemogram [white blood cell (WBC), red blood cell (RBC), platelet, hemoglobin, hematocrit] parameters. Materials and Methods: In the study, 10 Merino yearling received marbofloxacin (10 mg/kg/day, subcutan) for 14 days. Blood samples were taken on day 0 (control), 1, 3, 5, 7, 9, 11, 13 and 15 days. Sheep specific serum CK-MB and troponin I levels were measured with ELISA reader, while serum LDH, AST, ALT, ALP, GGT, total protein, creatinine and BUN values were determined with autoanalyser. Hemogram parameters were determined with hemocell counters, as well. Results: Marbofloxacin increased cardiac damage markers which were troponin I, not statistically significant (P>0,05), LDH and AST levels, statistically significant (P<0,05). While marbofloxacin did not cause (P<0,05) any adverse effect on liver function parameters, it caused (P<0,05) increase BUN levels and fluctuations in creatinine levels which were renal function values. In hemogram parameters, it caused (P <0,05) temporary decreases close to the reference values. Conclusion: It can be stated that the when sheep should be treated with high doses of long-term marbofloxacin, cardiotoxicity should be taken with caution. However, cardiotoxic effects of marbofloxacin should be confirmed histopathologically.